KONTRIBUSI HUMAN RELATIONS DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI INSTANSI PEMERINTAH: STUDI KASUS DI BPPMHKP PALEMBANG - Adillah, Cantika Fadiya; Saputra, Sepriadi; Arif Setiawan, Muhamad (JURNAL LENSA MUTIARA KOMUNIKASI, 2025)
This study aims to examine the contribution of human relations in enhancing employee work motivation within government institutions, particularly at the Agency for the Control and Supervision of Marine and Fishery Product Quality (BPPMHKP) in Palembang City. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The research is grounded in Abraham Maslow’s hierarchy of needs theory and the ten principles of human relations proposed by Sondang P. Siagian. The findings reveal that the implementation of human relations practices at BPPMHKP Palembang positively influences employee motivation. Harmonious working relationships, recognition of employee contributions, and open communication are identified as key factors that drive enthusiasm and productivity among employees. Nevertheless, several challenges persist, such as uneven workloads and limited access to training programs, which require further managerial attention. This study concludes that effective human relations can serve as a strategic approach to fostering a supportive and motivating work environment within the public sector